Satire as a form of native resistance in Mongo Beti's selected novels - Sani, Abubakar Mohammed (2016)
This study explores the impacts of colonialism on the political, economic and social life of the colonized native subjects through analyzing the selected novels by Mongo Beti. Despite the resistance, and struggle for independence by the postcolonial countries to decolonize their lands and people from the colonial occupation and their success in driving the colonizers out of their countries, they did not succeed in separating themselves from the political, social and economic influence of the imperialists. Thus, the people are disillusioned immediately after the so much desired and hard earned independence from the colonizers. The independence which promised so much has turned out to be a chimera as the situation in many African countries has deteriorated leading to socio-economic and political instability. These so-called independent countries are bedevilled with corruption, civil wars, political turmoil, among other factors due to absence of patriotism on the part of the indigenous people and external control from the ―former colonial masters‖. Through the use of satire, Mongo Beti portrays and criticizes these situations in one of the African countries in his literary works selected for this study (The Poor Christ of Bomba, King Lazarus, Remember Ruben and The Story of the Madman). Therefore, through the postcolonial concept of Native resistance by Frantz Fanon and by analysing the themes and characterizations of the selected novels by Mongo Beti, the researcher highlights the impacts of colonialism on the colonized native subjects represented by mimicry, identity crisis, political turmoil, corruption, resistance, among others. The novelist, Mongo Beti has his own understanding related to the impact of colonialism on the colonized native subjects in Cameroon. Thus, the study proves that the French colonial power triumphs its victory over the colonized native subjects in Cameroon as depicted in the selected novels.